2013
DOI: 10.1016/j.jpeds.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Morbidities in Very Low Birth Weight Infants

Abstract: Objective The objective of this study was to determine the association between direct costs for the initial neonatal intensive care unit (NICU) hospitalization and four potentially preventable morbidities in a retrospective cohort of very low birth weight infants (VLBW; <1500g birth weight). Methods The sample included 425 VLBW infants born alive between July 2005 and June 2009 at Rush University Medical Center. Morbidities included brain injury, necrotizing enterocolitis, bronchopulmonary dysplasia, and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
127
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(139 citation statements)
references
References 31 publications
2
127
0
10
Order By: Relevance
“…15 The intrinsic costs of surgical NEC, or marginal costs, have been estimated to be between $22 328 and $198 040. 10,28 The intrinsic costs of surgical NEC thus account for a fraction of the total costs of care once comorbidities are accounted for. The equivalence in cost between patients treated with peritoneal drainage alone and laparotomy alone in this study is likely a result of using matched cohorts with equivalent comorbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…15 The intrinsic costs of surgical NEC, or marginal costs, have been estimated to be between $22 328 and $198 040. 10,28 The intrinsic costs of surgical NEC thus account for a fraction of the total costs of care once comorbidities are accounted for. The equivalence in cost between patients treated with peritoneal drainage alone and laparotomy alone in this study is likely a result of using matched cohorts with equivalent comorbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of neonatal intensive care has been well described and comes as no surprise. 20,21 Hospitalizations for neonatal complications continue through the first year of life, costing $740 million annually. 22 The median hospitalization costs for infants with neonatal complications is .10 times higher than any other MDC in any of the age strata.…”
Section: Discussionmentioning
confidence: 99%
“…According to the definition of low birth weight provided by world health organization (WHO), low birth weight (LBW) refers to the birth weight less than 2500 grams (2,3). Due to greater sensitivity, lower immunity and an increased risk family and community, impose great costs on different diseases (4). Studies have shown that more than 20 million babies, 15.5% of all the births worldwide, are annually born with low weight, and that amount is 18.6% in underdeveloped countries, 16.5% in developing countries, and 7% in the developed countries (2).…”
Section: Introductionmentioning
confidence: 99%
“…They suffer from extremely high rates of morbidity and mortality from infectious diseases and underweight, and stunting or wasting beginning in the neonatal period and lasting through childhood (6). LBW is a multi-causal phenomenon that economic, social, and cultural factors contribute to its development, but the factors associated with the mother and the baby are the most important ones (4). Many researchers consider the following factors very effective on LBW which have many negative consequences: maternal age less than 20 years and more than 35 years, maternal smoking during the pregnancy, gestational age less than 37 weeks, lack of weight gain during the pregnancy (5), multiple pregnancy, birth interval of less than 3 years, lack of supplements during the pregnancy (6), maternal chronic diseases (7-9), preeclampsia (10)(11)(12)(13), birth of children with low weight (3), premature birth (14,15), growth retardation intra uterine (16) the pregnancy (17)(18)(19), renal and heart disease (20,21), diabetes (22), sex of the neonate, inadequate antenatal care service utilization and unwanted pregnancy (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation